Epidemiology of the use of addictive substances in the Colombo district, Sri Lanka. - Tissera, H.A (My University, 2005)
This study has four specific objectives focused on: estimating the prevalence of addictive substance use among persons 15-49 years, describing the socio-demographic and behavioral correlates among current substance users, estimating the prevalence of injecting drug use (IDU), and determining the prevalence of selected bio-markers of risk behavior among substance users. The study consisted of two components. A community based survey of 2500 persons between 15-49 years, selected using a multistage stratified cluster sampling procedure. In the second component respondent-driven sampling (RDS) was used to identify 250 current drug users and to estimate their characteristics especially injecting drug use. The study demonstrates that most start with smoking, go on to alcohol use and. then on to abuse of other illicit substances. Risk factors for other substance use were age over 35 years, male and married, urban dweller, predominantly Sinhalese and Buddhist, education level below G.C.E A/L, elementary employment with monthly income below Rs. 10,000.00. The study identifies alcohol abuse as a problem needing urgent attention and the community of drug users as a group who should be included in routine behavioral surveillance.